2021
DOI: 10.32491/jii.v21i1.548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented rice bran concentration using Lactobacillus sp in artificial feed on growth performance and enzyme activity of tilapia Oreochromis niloticus (Linnaeus, 1758)

Abstract: This study aims to determine the effect of the dose of fermented rice bran using Lactobacillus sp. on growth performance and enzyme activity in tilapia. This research was conducted in Sidenreng Rappang Regency. The test animal used was tilapia larvae measuring 1.17 g. The maintenance container is a tarp pool with a size of 1 m x 1 m x 1 m filled with fresh water as much as 85 L. The study was designed using a completely randomized design consisting of four treatments and three replications, thus there were 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Among these studies have been reported by [19], the use of 30% fermented rice bran using Aspergillus niger can be used as raw material for tilapia feed because it shows the best results in increasing digestibility and growth. then tilapia fed a feed containing 20% fermented rice bran gave a significant effect on the specific growth rate, protease and amylase enzyme activity [20]. Based on the research report, when juxtaposed with this study, it was shown that the use of fermented bran as a raw material for tilapia fish feed was more effective than the combination of fermented bran and commercial feed.…”
Section: Fish Growthsupporting
confidence: 51%
“…Among these studies have been reported by [19], the use of 30% fermented rice bran using Aspergillus niger can be used as raw material for tilapia feed because it shows the best results in increasing digestibility and growth. then tilapia fed a feed containing 20% fermented rice bran gave a significant effect on the specific growth rate, protease and amylase enzyme activity [20]. Based on the research report, when juxtaposed with this study, it was shown that the use of fermented bran as a raw material for tilapia fish feed was more effective than the combination of fermented bran and commercial feed.…”
Section: Fish Growthsupporting
confidence: 51%